2018
DOI: 10.1136/bmjopen-2017-019305
|View full text |Cite
|
Sign up to set email alerts
|

Online versus paper-based screening for depression and anxiety in adults with cystic fibrosis in Ireland: a cross-sectional exploratory study

Abstract: ObjectiveTo compare online and paper-based screening for depression and anxiety in adults with cystic fibrosis (CF).Design and settingCross-sectional study in CF clinics in Ireland and through the Cystic Fibrosis Ireland online community.Participants160 adult patients aged 18 or above were recruited. Of these, 147 were included in the analysis; 83 online and 64 paper-based. The remaining 13 were excluded because of incomplete data.MeasuresDepression and anxiety were measured using the Hospital Anxiety and Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
(52 reference statements)
2
21
0
1
Order By: Relevance
“…35 Although data from nonresponders were not available for comparison, data analysis conducted on the online and clinic samples yielded comparable findings. 21 Second, the physical health predictors used, FEV 1 % and BMI, were self-reported, and cross-checking with medical notes was not feasible due to resource constraints. In addition, these predictors may not have fully captured physical health status for all the participants because previous studies have indicated recent pulmonary exacerbations may also predict HRQOL in people with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Although data from nonresponders were not available for comparison, data analysis conducted on the online and clinic samples yielded comparable findings. 21 Second, the physical health predictors used, FEV 1 % and BMI, were self-reported, and cross-checking with medical notes was not feasible due to resource constraints. In addition, these predictors may not have fully captured physical health status for all the participants because previous studies have indicated recent pulmonary exacerbations may also predict HRQOL in people with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges associated with access and data collection in clinics resulted in slow recruitment, and, consequently, the decision was made to also recruit online. 21 An e-mail link to the questionnaire was sent by the charity Cystic Fibrosis Ireland to its community network of 345 adults with cystic fibrosis. The online version of the questionnaire was developed and administered by using the cloud-based software SurveyMonkey (at SurveyMonkey.com, San Mateo, California).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of this study include being the first study we are aware of to explore general community views on DURC, and the use of a before-and-after design to measure baseline views and changes following provision of information. The use of an established online community surveying methodology with a representative community sample is also a strength, as it is more convenient for participants and provides similar representativeness and results to paper-based surveys 48. The limitations of this study include the potential of bias in the framing of the survey, but we aimed to minimise this in our design.…”
Section: Discussionmentioning
confidence: 99%
“…There are some publications about the possibilities of using online-HADS-D for assessing depressive symptoms, but only in specific cohorts: in patients with cystic fibrosis [12] and in patients with tinnitus [13]. The potential of the online version of HADS as a screening tool for the detection and phenotyping of depression in the general population has not yet been explored.…”
mentioning
confidence: 99%